2018
DOI: 10.1037/ser0000224
|View full text |Cite
|
Sign up to set email alerts
|

Pilot trial of post-admission cognitive therapy: Inpatient program for suicide prevention.

Abstract: Suicide remains a significant public health problem for the United States military. Trauma-related diagnoses such as acute stress disorder (ASD) or posttraumatic stress disorder (PTSD) may exacerbate suicide risk, particularly among service members psychiatrically hospitalized following suicide-related events. To date, treatments to address suicide risk and trauma symptomatology among service members within inpatient milieus have been nonexistent. To address this gap, a randomized controlled pilot trial of Pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 36 publications
0
26
0
2
Order By: Relevance
“…Interventions were conducted on both adult wards 49 , 50 , 54 , 56 , 58 70 and adolescent in-patient wards. 43 , 51 53 , 55 , 57 Many wards did not have any gender restrictions ( n = 10), 49 , 50 , 53 – 56 , 58 , 60 , 69 , 70 but a few studies conducted interventions on female-only ( n = 3) 62 , 65 , 66 or male-only psychiatric ward ( n = 1), 63 or did not report the gender of the ward ( n = 7).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interventions were conducted on both adult wards 49 , 50 , 54 , 56 , 58 70 and adolescent in-patient wards. 43 , 51 53 , 55 , 57 Many wards did not have any gender restrictions ( n = 10), 49 , 50 , 53 – 56 , 58 , 60 , 69 , 70 but a few studies conducted interventions on female-only ( n = 3) 62 , 65 , 66 or male-only psychiatric ward ( n = 1), 63 or did not report the gender of the ward ( n = 7).…”
Section: Resultsmentioning
confidence: 99%
“… 52 , 57 , 59 , 61 , 64 , 67 , 68 In total, 62 in-patient psychiatric wards were included in the present review. Many of these were acute psychiatric wards ( n = 41), 49 , 54 , 56 , 58 63 , 65 70 followed by forensic ( n = 6), 64 child and adolescent wards ( n = 7), 43 , 51 53 , 55 , 57 PICU ( n = 4) 60 and triage/assessment units ( n = 3). 60 One study did not report the number or type of wards.…”
Section: Resultsmentioning
confidence: 99%
“…We identified two trials that evaluated PACT for the prevention of suicidal behavior in the postadmission acute phase. [4849] Both the trials reported significant reductions in depression, hopelessness, and posttraumatic stress disorder scores. But, only one of them reported a significant reduction in suicidal ideas.…”
Section: Resultsmentioning
confidence: 99%
“…The protocol was adapted from individual face-to-face therapy as described by Ghahramanlou-Holloway et al [11,12] for preventing repeat suicide attempts and known as Post-Admission Cognitive Therapy (PACT). In reference to this work, we named our program GPACTS.…”
Section: Description Of Cognitive Behavioural Group Therapymentioning
confidence: 99%